Case Study of Pronunciation and Punctuation Skills in Elementary School Students during a Pandemic: Studi Kasus Kemampuan Pelafalan dan Tanda Baca pada Siswa Sekolah Dasar pada Saat Pandemi - Natul, Baiyyi; Setyawati, Enik (Universitas Muhammadiyah Sidoarjo, 2022)
The researchers conducted it at SDN BanjarBendo, there were still errors in the use of punctuation and pronunciation in reading, especially in class III SDN BanjarBendo. Pronunciation and punctuation skills are very important in reading in order to know the meaning of the reading. The formulation in this study is how the pronunciation and punctuation skills of BanjarBendo Elementary School students during a pandemic. The purpose of this study was to analyze the pronunciation and punctuation skills of 3rd graders at SDN BanjarBendo. This study uses a case study qualitative research method with three research subjects. The instrument in this study consisted of observation, interviews and documentation in the form of photos and videos, while testing the validity of the data using triangulation techniques. The data analysis technique uses data reduction data presentation and withdrawal. conclusions based on the results of the study it can be found that 1 student subject is complete or able to use punctuation well, while 2 other student subjects have not used punctuation well.